Prevalence of thyroid-related abnormalities in adults with celiac disease: a cross-sectional study - Silva, Tatiana Sudbrack da Gama e; Corte, Bruno Pellini; Laporte, Paola Paganella; Meurer, Luise; Furlanetto, Tania Weber (Clinical and Biomedical Research, 2013)